Insertion angle of orthodontic mini-implants and their biomechanical performance: finite element analysis - Arantes,Vinícius de Oliveira Rossi (2015)
AbstractObjectiveThe aim of this study was to assess the stresses and strains generated after the application of two types of forces (traction of 200 gf and torsion of 20 N.cm) in two types of orthodontic mini-implants inserted at different (45° and 90° to the cortical bone) angles.Material and methodthree-dimensional models of two brands of mini-implant (SIN – Sao Paulo, Brazil, and RMO – South Korea) were exported and analyzed by finite element analysis (FEA). Analyses were performed on simulations of cortical bone, cancellous bone and the screw.ResultFEA analysis showed that RMO mini-implants had greater elastic deformation when subjected to tensile and torsional forces when compared with SIN mini-implants. For both trademarks and insertion angles tested, there was greater cortical bone deformation, but with the greatest strain located on the mini-implant. Tension on the mini-implant was located in its transmucosal profile region.ConclusionWhen comparing the two brands of mini-implants by FEA, it is fair to conclude that that the larger number of threads and their greater angle of inclination resulted in less resistance to deformation and induced a higher level of tension in the mini-implant and cortical bone when subjected to forces, especially when inserted at an angle of 45º to the cortical bone.